New Evidence for the Role of Pituitary Adenylate Cyclase-Activating Polypeptide as an Antimicrobial Peptide in Teleost Fish - Janet Velázquez; Tania Rodríguez-Cornejo; Tania Rodríguez-Ramos; Geysi Pérez-Rodríguez; Laura Rivera; James Hugh Campbell; Lowia Al-Hussinee; Yamila Carpio; Mario Pablo Estrada; Brian Dixon (MDPI AG, 2023)
Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) is a multifunctional neuropeptide that is widely distributed and conserved across species. We have previously shown that in teleost fish, PACAP not only possesses direct antimicrobial properties but also immunomodulatory effects against the bacterial pathogens Flavobacterium psychrophilum and Pseudomonas aeruginosa using in vitro and in vivo experiments. These previous results suggest PACAP can be used as an alternative to antibiotics to prevent and/or treat bacterial infections in the aquaculture industry. To accomplish this goal, more studies are needed to better understand the effect of PACAP on pathogens affecting fish in live infections. In the present study, the transcripts PACAP, PRP/PACAP, and VPAC2 receptor were examined in rainbow trout (Oncorhynchus mykiss) naturally infected with Yersinia ruckeri, which exhibited an increase in their expression in the spleen when compared to healthy fish. Synthetic Clarias gariepinus PACAP-38 has direct antimicrobial activity on Y. ruckeri and inhibits up to 60% of the bacterial growth when the peptide is at concentrations between 50 and 100 µM in TSB. The growth inhibition increased up to 90% in the presence of 12.5 µM of PACAP-38 when salt-free LB broth was used instead of TSB. It was also found to inhibit Y. ruckeri growth in a dose-dependent manner when the rainbow trout monocyte/macrophage-like cell line (RTS11) was pre-treated with lower concentrations of the peptide (0.02 and 0.1 µM) before going through infection. Differential gene expression was analyzed in this in vitro model. Overall, the results revealed new evidence to support the role of PACAP as an antimicrobial and immunomodulatory peptide treatment in teleosts.